PENGARUH SENAM KAKI TERHADAP SENSITIVITAS KAKI PADA PENDERITA DIABETES MELITUS DI PUSKESMAS MEDAN TUNTUNGAN TAHUN 2015 - Silalahi, Elny Lorensi; Ginting, Surita; Marpaung, Anita Johana (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2015)
Gymnastic of foot is activity or practice for the patient for the patient with diabetes mellitus to prevent the injury and for the blood circulation on foot (Suryadi, 2004). The objective of foot gymnastic is to improve the blood circulation on the foot of patient with diabetes mellitus for the circulation of nutrition on the organ (Tara, 2003). Sensitivity of foot is sensitivity on the lower extremity. This research applies pretest-posttest design in wich this research was conducted by do the initial observation (ptetest) before the intervention. After the intervention, the observation is conducted from the observation sheet. The resulth of research  before the intervention of foot gymnastic indicates that the less sensitivity is 15 respondents (50%), medium sensitivity is 8 respondents (26,7%), good sensitivity for 7 respondent (23,3%) and after the intervention of foot sensitivity, the medium sensitivity to be 18 respondent (78,3%), good sensitivity for  5 respondents (21,7%). The result of statistical test has a significant result to the increasing of sensitivity of foot where p = 0,00 with the average value of increasing is 0,67.